2020
DOI: 10.1021/jacs.0c07291
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Chiral Self-Assembly of Cone-Shaped Subphthalocyanine Aromatics

Abstract: Columnar polymers and liquid crystals obtained from π-conjugated cone-shaped molecules are rising increasing interest due to the possibility of obtaining unconventional polar organizations that show anisotropic charge transport and unique chiroptical properties. However, and in contrast to the more common planar discotics, the self-assembly of conic or pyramidic molecules in solution remains largely unexplored. Here, we show how a molecular geometry change, from flat to conic, can generate supramolecular lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 116 publications
0
32
0
1
Order By: Relevance
“…Nakashima et al reported a method to tune aggregate length and morphology by balancing the enantiomeric excess (ee) of the components, leading to heterochiral dimers in racemic mixtures or homochiral polymers at high ee’s 39 . Another remarkable example reported the use of topological chirality to achieve narcissistic self-sorting into homochiral dimers, but social self-sorting into a heterochiral polymer with alternating microstructure 40 . Seminal work by George et al demonstrated chirality driven self-sorting and stereoselective seeded supramolecular polymerizations with a series of naphthalene diimide (NDI) functionalized monomers 30 , 31 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Nakashima et al reported a method to tune aggregate length and morphology by balancing the enantiomeric excess (ee) of the components, leading to heterochiral dimers in racemic mixtures or homochiral polymers at high ee’s 39 . Another remarkable example reported the use of topological chirality to achieve narcissistic self-sorting into homochiral dimers, but social self-sorting into a heterochiral polymer with alternating microstructure 40 . Seminal work by George et al demonstrated chirality driven self-sorting and stereoselective seeded supramolecular polymerizations with a series of naphthalene diimide (NDI) functionalized monomers 30 , 31 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in the supramolecular polymerization of a chiral subphthalo­cyanine derivative, Ortí, Torres, González-Rodríguez, and co-workers computationally suggested that chain growth proceeds in an alternating heterochiral manner. This possibility is interesting, but the authors did not exclude the possibility of concomitant homochiral chain growth because even the enantiomerically pure monomer alone can polymerize under the same conditions …”
Section: Introductionmentioning
confidence: 99%
“…5a) in both polar and nonpolar aliphatic solvents. 72 In polar aliphatic solvents, 1P and 1M formed self-sorting homochiral dimers in a tail-to-tail manner, in which the molecules had the closest distance and lowest energy according to calculations (Fig. 5b).…”
Section: Chirality Differencementioning
confidence: 96%